1992
DOI: 10.1007/bf01957751
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory cytokines in measles: Correlation between serum interferon-γ levels and lymphocyte subpopulations

Abstract: Abstract. , tumour necrosis factor alpha (TNF-a) and interferon gamma (IFN-7) were measured in serum from children with measles using an immunoradiometric assay. The IFN-7 level was increased in 52 out of 54 patients in the acute phase of measles (< 7 days of illness), and then declined to an undetectable level in the convalescent phase. Neither IL-1 nor TNF could be detected during the course of the illness. The mean serum IFN-7 level was at its peak on day 4 and could be detected over a 7-day period after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Interestingly, Th1-type cytokines (IFN-␥ and IL-2) were induced in all monkeys irrespective of the IL-12 level. The induction of IFN-␥ in plasma at early time points is consistent with that in previous studies of human measles (10,19,24,41). A previous study showed no significant induction of IL-2, IL-12, and IFN-␥ in monkeys infected with wild-type MV (4).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Th1-type cytokines (IFN-␥ and IL-2) were induced in all monkeys irrespective of the IL-12 level. The induction of IFN-␥ in plasma at early time points is consistent with that in previous studies of human measles (10,19,24,41). A previous study showed no significant induction of IL-2, IL-12, and IFN-␥ in monkeys infected with wild-type MV (4).…”
Section: Discussionsupporting
confidence: 90%
“…IFN‐γ has been found to be elevated in measles, rubella, and parvovirus infection79 and in PBMCs of infected autologous or allogenic mumps virus‐infected target cells 80. Also, IFN‐γ levels in the serum are increased in patients in the acute phase of measles 81. Mumps virus, a virus often associated with type 1 diabetes, also brings autoimmune complications, such as orchitis.…”
Section: Pre‐autoimmune Diseasementioning
confidence: 89%
“…" Sensitive immunoassays have shown appreciable concentrations of these cytokines in serum/plasma or effusions from the patients with some reactive or neoplastic disorders. [5][6][7][8][9] Recent reports indicate that IL-13, TNF-ot, platelet activating factor, IFN--y, and IL-6 are increased in the cerebrospinal fluid of patients with meningitis,1013 however, their clinical and biological roles are not fully elucidated.…”
mentioning
confidence: 99%